CHISUNGU - Richards, Audrey. ([S.l.])
1 online resource
Keywords: Audrey Richards (1899-1984) was a leading British anthropologist of the twentieth century and the first woman president of the Royal Anthropological Institute. Based on fieldwork conducted at a time when the discipline was dominated by male anthropologists, Chisungu: A Girl's Initiation Ceremony Among the Bemba of Zambia is widely hailed as a classic of anthropology and African and gender studies. Underpinned by painstaking research carried out by Richards among the Bemba people in northern Zambia in the 1930s, Chisungu focuses on the initiation ceremonies for young Bemba girls. Pioneering the study of women's rituals and challenging the prevailing theory that rites of passage served merely to transfer individuals from one status to another, Richards writes about the incredibly rich and diverse aspects of ritual that characterised Chisungu: its concern with matriliny; deference to elders; sex and reproduction; the birth of children; ideas about the continuity between past, present and future; and the centrality of emotional conflict. On a deeper level, Chisungu is a crucial work for the role it accords to the meaning of symbolism in explaining the structure of society, paving the way for much subsequent understanding of the role of symbolic meaning and kinship. This Routledge Classics edition includes a new foreword by Jessica Johnson and an introduction by Jean La Fontaine.